Involvement of PPARs in Cell Proliferation and Apoptosis in Human Colon Cancer Specimens and in Normal and Cancer Cell Lines. (13th March 2007) - Martinasso, G.; Oraldi, M.; Trombetta, A.; Maggiora, M.; Bertetto, O.; Canuto, R. A.; Muzio, G.
Abstract : PPAR involvement in cell growth was investigated "in vivo" and "in vitro" and was correlated with cell proliferation and apoptotic death. "In vivo" PPARγ andα were evaluated in colon cancer specimens and adjacent nonneoplastic colonic mucosa. PPARγ increased in most cancer specimens versus mucosa, with a decrease in c-Myc and in PCNA proteins, suggesting that colon cancer growth is due to increased cell survival rather than increased proliferation. The prevalence of survival over proliferation was confirmed by Bcl-2 or Bcl-X L increase in cancer versus mucosa, and by decreased PPARα . "In vitro" PPARγ and PPARα were evaluated in human tumor and normal cell lines, treated with natural or synthetic ligands. PPARγ was involved in inhibiting cell proliferation with a decrease in c-Myc protein, whereas PPARα was involved in inducing apoptosis with modulation of Bcl-2 and Bad proteins. This involvement was confirmed using specific antagonists of two PPARs. Moreover, the results obtained on treating cell lines with PPAR ligands confirm observations in colon cancer: there is an inverse correlation between PPARα and Bcl-2 and between PPARγ and c-Myc.